2017
DOI: 10.1111/avsc.12345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire regime on plant species richness and composition differ among forest, woodland and heath vegetation

Abstract: Question: Do the effects of fire regimes on plant species richness and composition differ among floristically similar vegetation types?Location: Booderee National Park, south-eastern Australia. Methods:We completed floristic surveys of 87 sites in Sydney Coastal dry sclerophyll vegetation, where fire history records have been maintained for over 55 years. We tested for associations between different aspects of the recent fire history and plant species richness and composition, and whether these relationships w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 60 publications
4
28
1
1
Order By: Relevance
“…The results regarding richness and diversity of species of this study were similar to some previous studies where it was found that fire do not affect trees diversity and on the contrary enhance species number in some cases, being considered as a significant evolutionary force (Keeley et al 2011, Gallegos-Rodríguez et al 2014, Hedo et al 2015, Pereira et al 2016, Foster et al 2017. The diversity of the fumigated area was similar to the control area but lower to the other areas.…”
Section: Discussionsupporting
confidence: 88%
“…The results regarding richness and diversity of species of this study were similar to some previous studies where it was found that fire do not affect trees diversity and on the contrary enhance species number in some cases, being considered as a significant evolutionary force (Keeley et al 2011, Gallegos-Rodríguez et al 2014, Hedo et al 2015, Pereira et al 2016, Foster et al 2017. The diversity of the fumigated area was similar to the control area but lower to the other areas.…”
Section: Discussionsupporting
confidence: 88%
“…Tipe hutan ini sangat rentan terhadap kerusakan dan jika hutan kerangas mengalami kerusakan/degradasi lahan, maka akan sulit dipulihkan, terlebih secara alami (Kissinger et al, 2013). Hal ini dikarenakan pemulihan hutan setelah kerusakan dipengaruhi faktor-faktor antara lain tipe hutan, struktur vegetasi, tingkat dan intensitas gangguan, manajemen pengelolaan serta faktor biotik dan abiotik dari karakteristik hutan tersebut (Foster et al, 2018).…”
Section: Pendahuluanunclassified
“…Notably, it will be diffi cult to develop a management plan that will benefi t every organism in a community. Previous studies have revealed that there are variations in the way species respond to fi res -for example, some plants need regular fi res to germinate, whereas other plants face diffi culties in re-sprouting after a fi re [5]. Physiological research can aid in understanding the dynamics of population response by revealing the conditions needed for each species to thrive, the physiological mechanisms species employ to survive fi re, and how organisms use energy in response to an altered habitat.…”
Section: A Physiological Understanding Of Organismal Responses To Fi Rementioning
confidence: 99%